The Polish crisis 1980-1982 from the Western perspective - Długołęcki, Piotr (2022)
The 112 archival documents in this collection concern the situation in Poland in the years 1980-1982. The archival material included illustrates the so-called Polish crisis – a series of events that were crucial for the situation within Poland, and yet were also a highly important aspect of international relations at that time. The aim of this publication is to show the Polish Crisis from the viewpoint of countries which were part of the Western Bloc, in the then bi-polar world. The addition of documents from the NATO Archive showing the policy of the North Atlantic Alliance provides a fuller image of western countries’ reaction to events in Poland. The documents show the common features and divergent elements of Western countries’ policies with regard to the crisis in Poland and present the specific nature of the individual countries’ relations with Poland, as well as to illustrate the counter-measures taken by the Polish communist authorities in response to Western actions. This publication contains archival material from Australia, Austria, Canada, France, Germany, Greece, Ireland, Israel, Italy, NATO, the Netherlands, Poland, Turkey, the United Kingdom and the United States. The vast majority of these documents have not been published before